2021
DOI: 10.1002/cjce.24028
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of solids concentration optical fibre probes with solids‐polymer blocks

Abstract: Owing to the determinant effects of the local distribution of solids concentration on transport phenomena, particularly in gas‐solids flows in such processing units as gas‐solid fluidized beds and pneumatic conveying lines, its accurate measurement has received considerable attention. Despite the widespread applications of optical fibre probes for the measurement of local solids concentration, these instruments may create measurement uncertainties due to their structural designs and challenges in their accurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…From the data in Figure 3, we see that u cf decreases as the temperature is increased (0.83‐0.93 cm/s at 25°C; 0.78‐0.85 cm/s at 300°C; 0.65‐0.76 cm/s at 600°C). These results are in part due to the increase in dynamic viscosity and the decrease of the density of air used as fluidizing agent, [ 23,24 ] and the reduction in the agglomerate density as a result of the mass loss. The change in u cf is also the result of the growth of the agglomerates as the temperature increases and approaches the melting temperature of Li 2 CO 3 (723°C).…”
Section: Resultsmentioning
confidence: 99%
“…From the data in Figure 3, we see that u cf decreases as the temperature is increased (0.83‐0.93 cm/s at 25°C; 0.78‐0.85 cm/s at 300°C; 0.65‐0.76 cm/s at 600°C). These results are in part due to the increase in dynamic viscosity and the decrease of the density of air used as fluidizing agent, [ 23,24 ] and the reduction in the agglomerate density as a result of the mass loss. The change in u cf is also the result of the growth of the agglomerates as the temperature increases and approaches the melting temperature of Li 2 CO 3 (723°C).…”
Section: Resultsmentioning
confidence: 99%
“…We are pleased to report that 30 papers were initially submitted to the journal and after peer review, following the standard journal procedures, 28 papers were accepted. Due to the page limitation of each issue, we have decided to publish a full special issue with 16 papers as Part 1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and a special section in the coming issue (vol. 99, issue 12) with 12 papers as Part II.…”
mentioning
confidence: 99%
“…[ 15 ] Shabanian and Chaouki found a moderate interparticle force, which could contain smaller bubbles, in a cohesive bed compared with a non‐cohesive bed. [ 16 ] Zhong et al reported that higher liquid viscosity resulted in higher fountain height and non‐uniform distribution in the fountain centre and provided an efficient method to simulate wet fluidization with the two‐fluid model. [ 17 ] Generally, wet particles are harder to fluidize due to the attenuation of kinetic energy during the process of particle collisions.…”
Section: Introductionmentioning
confidence: 99%